Evaluation of potential drug–drug interactions among patients with chronic kidney disease in northeastern Nigeria - Okoro, Roland N; Farate, Victor T (African Journal of Nephrology, 2019)
Background: Potential drug–drug interactions (pDDIs) may not manifest clinically in patients who are treated with multiple pharmaceutical agents, but when they do they can produce adverse outcomes. In patients with chronic kidney disease (CKD), the frequent use of multiple agents to manage this condition and its complications puts these patients at increased risk for DDIs. We determined the prevalence of pDDIs in CKD patients in two Nigerian hospitals and investigated possible predictors of pDDIs. Methods: This cross-sectional study involved patients with CKD who attended the nephrology unit of the University of Maiduguri Teaching Hospital and the medical outpatients clinic of the State Specialist Hospital in Maiduguri, Nigeria. We collected prescriptions, clinical data and laboratory data from the medical files of patients seen between January 2013 and December 2017. Descriptive and inferential statistics were used to analyse the data. Results: The study included 201 patients. A total of 273 pDDIs were identified in 166 patients (83%). These pDDIs included 30 unique drug interactions, the most common being between ferrous sulphate and calcium carbonate (seen in 46% of patients with pDDIs), followed by lisinopril and furosemide (8%). The proportion of clinically significant interactions was only 2%. There was a positive association between pDDIs and the total number of drugs prescribed (P < 0.001). Conclusions: A high prevalence of pDDIs was documented among Nigerian patients with CKD. The bulk of the interactions were related to the co-prescription of ferrous sulphate and calcium carbonate. The total number of drugs prescribed was a significant predictor of pDDIs. We recommend routine screening of prescriptions of CKD patients for potential pDDIs.